Hypothermic perfusion hepatectomy for unresectable liver cancer: A single‐center experience. (13th November 2019) - Yoon, Young‐In; Lee, Sung‐Gyu; Moon, Deok‐Bog; Kim, Ki‐Hun; Park, Cheon‐Soo; Park, Gil‐Chun; Cho, Yong‐Pil
Abstract: Background: The resection of liver tumors that involve the hepatic veins adjacent to the vena cava or hepatic hilum is technically challenging. We present our surgical techniques and the long‐term outcome of five patients with conventionally unresectable tumors. Methods: Five patients with conventionally unresectable tumors were successfully treated by "ex‐situ liver resection" and "in‐situ and ante‐situm hypothermic liver perfusion" under total vascular exclusion and venovenous bypass. Results: These approaches allowed complete tumor removal with vascular reconstruction under a bloodless surgical field, while minimizing hepatic ischemic injury and preserving liver function. No perioperative mortalities occurred, and postoperative complications were minimal. The postoperative survival periods were limited due to the advanced malignancies in our patients, but the survival benefit was encouraging. The median postoperative survival time was 29.1 months, with the longest survival period being nearly 10 years. These approaches improved the quality of life and provided an opportunity for additional treatment. Conclusions: Hypothermic perfusion hepatectomy is a realistic option for achieving surgical cure or significantly improved survival and quality of life in patients with tumors deemed unresectable using conventional normothermic hepatectomy. These approaches can overcome the limitations of the liver's restricted normothermic ischemia tolerance or inaccessible tumor locations. Abstract : Highlight Some liver tumors are conventionally unresectable because of the liver's limited tolerance to long normothermic ischemia or inaccessible tumor location. Yoon and colleagues present their surgical technique and long‐term outcomes of five cases treated by in‐situ or ante‐situm hypothermic liver perfusion or ex‐situ liver resection under total vascular exclusion and venovenous bypass.